Symptomatic isolated terminal ileal ulcers: etiology and clinical significance - Mehta, Varun; Gupta, Ankita; Mahajan, Ramit; Narang, Vikram; Midha, Vandana; Sood, Neena; Kaur, Harpreet; Kaur, Kirandeep; Sood, Ajit (Endoscopy International Open, 2017)
Background With an increasing number of ileal intubations, isolated terminal ileal ulcers (ITIU) are frequently found during colonoscopies. The present study aimed at studying the etiology and clinical significance of these ulcers in patients having gastrointestinal symptoms.Methods This was a prospective observational study performed on consecutive patients who underwent ileocolonoscopy for various gastrointestinal symptoms between 1 January 2014 and 31 December 2014. Clinical, endoscopic, and histological findings of patients with ITIUs were assessed to determine the etiology and they were treated accordingly. Symptom resolution was assessed within 3 – 6 months of initial diagnosis, and colonoscopy was repeated for consenting patients.Results Among 74 (4.9 %) of 1497 patients who had ITIUs on ileocolonoscopy, 41 (55.4 %) had specific etiologies on initial testing. After 3 – 6 months follow-up, definitive diagnosis was ascertained in 44 (59.5 %) patients [Crohn’s disease (CD): 19 (25.7 %), NSAID-induced ulcers: 11 (14.9 %), intestinal tuberculosis (ITB): 9 (12.2 %), and eosinophilic enteritis: 5 (6.8 %)], and 30 patients (40.5 %) had nonspecific ulcers. After treatment, symptomatic and endoscopic resolution were noted in 55/60 patients (91.7 %) and 28/36 patients (77.8 %), respectively. Of 5/60 patients who remained symptomatic, three were initially diagnosed with nonspecific ulcers and two with CD, and they were finally diagnosed with CD and ITB respectively, and treated accordingly.Conclusions In patients with gastrointestinal symptoms, more than half of the ITIUs have specific etiologies, and timely diagnosis and appropriate treatment can prevent serious complications. Nonspecific ulcers can be managed with symptomatic treatment, but need close monitoring and re-evaluation in the case of persistence of symptoms.